Bacterial Filtration Using Carbon Nanotube/Antibiotic Buckypaper Membranes. (27th March 2013) - Sweetman, Luke J.; Alcock, Leighton J.; McArthur, Jason D.; Stewart, Elise M.; Triani, Gerry; in het Panhuis, Marc; Ralph, Stephen F.
Abstract : The preparation of free-standing carbon nanotube "buckypaper" (BP) membranes consisting of either single-walled carbon nanotubes (SWNTs) or multi-walled carbon nanotubes (MWNTs), and the antibiotic ciprofloxacin (cipro), is reported. The electrical, mechanical and morphological properties of these membranes have been characterised and are compared to those of the corresponding buckypaper membranes containing the surfactant Triton X-100 (Trix). Analysis of scanning electron microscopic images of the surfaces of SWNT/cipro and SWNT/Trix (Trix  =  Triton X-100) buckypapers revealed that the diameter of their surface pores was significantly smaller than that of the corresponding materials prepared using MWNTs. Similarly, the average internal pore diameter of both SWNT buckypapers was found to be smaller than that of their MWNT counterparts, after analysis of binding isotherms derived from nitrogen adsorption/desorption measurements performed on the materials. All four buckypaper membranes examined were found to be >99% effective for removing Escherichia coli ( E. coli ) from aqueous suspensions. However, buckypapers containing ciprofloxacin outperformed their counterparts containing the surfactant. Both MWNT buckypapers were more effective at preventing passage of E. coli than their analogues containing SWNTs, while fluorescence microscopic examination of stained membrane surfaces demonstrated that buckypapers composed of SWNTs had greater bactericidal properties.